Determinants of Instrumental extinction in terrestrial toads (Bufo arenarum) - Muzio, Ruben Nestor (2006)
Previous research in a water-reinforced instrumental training situation with toads (Bufo arenarum) has shown that performance in both acquisition and extinction is poorer after partial, rather than continuous reinforcement training. In Experiment 1, the performance of a group receiving 24 trials on a 50% partial reinforcement schedule was poorer in acquisition and extinction than that of continuously reinforced groups matched for trials or reinforcements. However, partially reinforced toads extinguished at the same rapid rate as a continuously reinforced group that received training only on the days in which the partial toads received water reinforcement. In Experiment 2, extinction was faster after 10 reinforced acquisition trials than after 30 trials. This evidence suggests that the deleterious effects of partial reinforcement in toads can be explained by a combination of two factors, namely, the distribution of reinforced trials across days and the total number of reinforcements.